Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Variasi dan Kombinasi Passing, Dribbling Sepak Bola Siswa Kelas X - Afrian Ahmad Fahrezi; Nanik Indahwati (Departement of Mathematics Education, 2024)
Problem based learning is a learning method that has critical thinking skills so that it can overcome problems by finding the right approach. The aim of this research is to determine the influence of the Problem based learning model on the learning outcomes of variations and combinations of passing and Dribbling in class X soccer. This research uses a quantitative approach and uses a Non-Randomized Control Group Pretest-posttest design. This research was conducted at SMKN 1 Buduran Sidoarjo using classes. X Clothing 3 as the experimental class and X Tourism Service Business as the control class. The instruments used are knowledge tests and skills tests. In this research, data analysis techniques were used, namely descriptive statistics, kolmogorov-smirnov normality test, homogeneity and non-parametric test (Mann-Whiteney U test). Based on data that has been tested using the Mann-Whiteney U test, the results obtained in the post-test value aspect of knowledge and passing skills for the control class & experimental class have a sig value (0.492 > 0.05) and the results for the post-test value for knowledge and Dribbling skills the control class & experimental class have a sig value (0.836 > 0.05). Based on these results, it was concluded that there was no influence between the Problem based learning model on the learning outcomes of variations and combinations of passing, Dribbling in class .